Effects of Individual Incentive Reforms in the Public Sector: The Case of Teachers - Pedro S. Martins; Jo\~ao R. Ferreira (Global Labor Organization (GLO), 2024)
We evaluate a political reform in Portugal that introduced individual teacher performancerelated pay and tournaments in public schools. We find that the focus on individual performance decreased student achievement, as measured in national exams, and increased grade inflation. The results follow from a difference-in-differences analysis of matched student-school panels and two complementary control groups: public schools in regions that were exposed to lighter reforms; and private schools, whose teachers had their incentives unchanged. Students in public schools with a higher proportion of teachers exposed to the tournament also perform worse. Overall, our results highlight the potential social costs from disruption of cooperation amongst public sector workers due to competition for promotions.
Keywords: I21; M52; I28; 330; Tournaments; Public Sector; Teacher Merit Pay; Matched School-Student Data